The Competitiveness of Polish Firms and the European Union Enlargement - Gorynia, Marian (Economics and Business Review, 2001)
This paper has two aims. The first one is to present a three-dimensional concept of the competitiveness of an enterprise. The concept of firm competitiveness discussed in the paper covers three dimensions: competitive position of an enterprise, competitive potential of an enterprise, competitive strategy of an enterprise. Each of the above-mentioned dimensions was subject to operationalisation sets of variables describing particular dimensions of firm competitiveness were suggested. The second aim of the paper is to present the results of empirical studies on the competitiveness of Polish firms in comparison with European Union firms in the light of Poland´s anticipated entry into the EU. The research is based on the concept of firm competitiveness developed in the first part of the paper. The studies, carried out in the year 2000, included 68 firms of the manufacturing industry registered in Poland. The results obtained indicate that, according to managers from the 68 enterprises, there is a significant competitive gap between the Polish firms and their rivals from the EU. This gap concerns all the three dimensions of firm competitiveness: competitive position, competitive potential and competitive strategy. (original abstract)